A New Educational Thermodynamic Software to Promote Critical Thinking in Youth Engineering Students (2019)
This article presents the application of a new educational thermodynamic software called MOLECULARDISORDER, based on graphical user interfaces created in Matlab® to promote critical thinking in youth engineering students, by means of the energy and entropy balance application in di erent systems. Statistics of the results obtained by the youth students are shown to determine the influence of the software in a regular course in thermodynamics to promote critical thinking. Two case studies were done by the students, where parameters such as temperature of the fluid and metal surfaces, pressure of the system, mass of the fluid and solid, volume, and velocity of the fluid are used to obtain output variables such as enthalpy, entropy, changes in entropy, entropy production, and energy transfer in the chosen system. Four cognitive skills were considered to evaluate the cognitive competencies of interpreting, arguing and proposing, and interacting with the di erent graphical user interfaces; these cognitive skills (CS) were argumentative claim (CS1), modeling (CS2), interpreting data/information (CS3), and organization (CS4). Student´s T-test was used to compare the degree of di culty of each criterion. The case studies were evaluated first without using the software and then with the use of the software to determine the significant e ect of the software quantitatively. A population of 130 youth students was taken to perform the statistical analysis with a level of significance of 5%. With the help of the software, the students obtained an improvement when performing case study 1 since the p-value obtained was 0.03, indicating that there are significant di erences between the results before and after taking the software. The overall averages of the grades for case study 1 had an increase after using the software from 3.74 to 4.04. The overall averages for case study 2 were also higher after taking the software from 3.44 to 3.75.